Change in Abdominal Morphology After Surgical Correction of Thoracolumbar Kyphosis Secondary to Ankylosing Spondylitis: A Computed Tomographic Study. Issue 23 (December 2015) - Ji, Ming-liang; Qian, Bang-ping; Qiu, Yong; Wang, Bin; Mao, Sai-hu; Zhu, Ze-zhang; Yu, Yang
Abstract : Study Design: A computed tomographic study. Objective: To investigate the change in abdominal morphology in surgically treated patients with ankylosing spondylitis (AS) and thoracolumbar kyphosis. Summary of Background Data: Severe thoracolumbar kyphosis in patients with AS exerts pressure on the abdominal cavity and subsequently causes intra-abdominal complications. Several spinal osteotomy techniques have been widely used to correct AS-related thoracolumbar kyphosis. To date, the changed abdominal morphology in patients with AS undergoing surgical correction of thoracolumbar kyphosis has not been addressed. Methods: A total of 29 patients with AS undergoing lumbar pedicle subtraction osteotomy for correction of thoracolumbar kyphosis were retrospectively reviewed. Computed tomographic scans of the spine were used to measure the longitudinal, transverse, and anterior–posterior diameters of the abdominal cavity. Furthermore, the abdominal cavity was considered as an ellipsoid structure, thereby allowing calculation of its volume. Radiographical evaluations included global kyphosis (GK), thoracic kyphosis, lumbar lordosis (LL), and angle of fusion levels (AFL). Results: The longitudinal diameter of abdominal cavity significantly increased (P < 0.01), whereas the transverse and anterior–posterior diameters of the abdominal cavity did not change, postoperatively ( P  > 0.05). Significant changes in GK, LL, and AFL were observed (P < 0.01). The abdominal cavity volume (ACV) increased by an average of 652 mL. The change in ACV was significantly correlated with the changes in GK (r = 0.453, P  = 0.014), LL (r = 0.42, P  = 0.023), and AFL (r = 0.388, P  = 0.037). Conclusion: The increased ACV after correction of thoracolumbar kyphosis was quantitatively confirmed by this study. Thus, the improvement in digestive function after correction of thoracolumbar kyphosis secondary to AS, which has been previously documented, may be because of an increase in ACV. Moreover, spine surgeons should be aware of the potential risk for the development of abdominal complications caused by the lengthening of longitudinal diameter of the abdominal cavity. Level of Evidence: 3